THE EFFECT OF GROWTH, PROFITABILITY, LEVERAGE, AND DIVIDEND ON COMPANY VALUE IN THE BUILDING AND NON-BUILDING CONSTRUCTION SUB -SECTORS AT BEI 2014 - 2020 - Tabita Deborah; Fitri Ismiyanti (Jurnal Ekonomi, 2023)
The era of the government of President-elect Joko Widodo in the two periods of Indonesian government in 2014 and 2019 brought fresh air to the infrastructure sector because one of the government's visions was to carry out development evenly, this had a positive impact on the construction industry. However, in 2020 when the Covid-19 pandemic began to hit Indonesia, all industrial sectors experienced a decline, without exception the construction sector. This study aims to determine the effect of company growth, profitability, leverage, and dividends on company value in the building and non-building construction sub-sector in 2014 - 2020. This period includes 3 different situations. The samples used were 9 issuers in the building and non-building construction sub-sector that met the criteria. The data used were time series data. The approach in this study is through descriptive statistical analysis and panel data regression analysis. The results obtained from this study are that growth has no effect and is negative on firm value, because when a company's growth moves fast it will have an impact on a decrease in firm value. Profitability has a positive and significant effect on firm value because the increase in company profits makes the investment return contribution high. Leverage has a positive and significant effect on firm value when DAR increases, it will make a positive signal that the company is developing its business. Dividends have a positive and significant effect on firm value when a high DPR will maximize firm value. Dividend distribution can reduce the effect of income uncertainty felt by investors.